1984
DOI: 10.1099/0022-1317-65-10-1713
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Nature of the Viroid-like RNA-2 of Solanum Nodiflorum Mottle Virus and the Ability of Other Plant Viruses to Support the Replication of Viroid-like RNA Molecules

Abstract: SUMMARYThe stock culture of solanum nodiflorum mottle virus (SNMV) was freed from RNA-2 by passage through single lesions induced in inoculated leaves of Nicotiana debneyi by dilute inocula of partially purified SNMV RNA-1. This isolate (S1) was indistinguishable serologically and in symptomatology from the stock culture of SNMV. Using a sensitive bioassay for detecting RNA-2, no SNMV RNA-2 was found in RNA from particles of the S1 isolate purified after three successive passages in Nicotiana clevelandii. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…These results were equivocal, however, because the necrotic lesions were few in number and/or difficult to detect, and symptoms were occasionally erratic. The work presented here provides evidence, via nucleic acid hybridization, that both TRosV and CfMV support the replication and packaging of LTSV RNA-2, confirming that this sat-RNA does not specifically require genomic LTSV RNA for replication (Paliwal, 1984b;Jones & Mayo, 1984). Other instances of nonspecificity in the interaction between helper sobemoviruses and sat-RNA have been reported.…”
Section: Lucerne Transient Streak Virus (Ltsv) Occurs Inmentioning
confidence: 51%
See 3 more Smart Citations
“…These results were equivocal, however, because the necrotic lesions were few in number and/or difficult to detect, and symptoms were occasionally erratic. The work presented here provides evidence, via nucleic acid hybridization, that both TRosV and CfMV support the replication and packaging of LTSV RNA-2, confirming that this sat-RNA does not specifically require genomic LTSV RNA for replication (Paliwal, 1984b;Jones & Mayo, 1984). Other instances of nonspecificity in the interaction between helper sobemoviruses and sat-RNA have been reported.…”
Section: Lucerne Transient Streak Virus (Ltsv) Occurs Inmentioning
confidence: 51%
“…In situ hybridization of viral RNA samples in dried 2 % agarose-formaldehyde gels showed that the high M r genomic RNAs from LTSV, CfMV and TRosV did not hybridize with the LTSV RNA-2 specific probe, suggesting that no sequence homology exists between these RNAs and LTSV sat-RNA (data not shown). Jones & Mayo (1984) observed that co-inoculation of TRosV and LTSV RNA-2 on Chenopodium quinoa resulted in an apparent change of lesion type, from chlorotic to necrotic, and this was considered to be due to LTSV RNA-2 replication in the presence of TRosV. A small proportion of the progeny virus from this mixed infection, following propagation in B. rapa, induced necrotic lesions on C. amaranticolor.…”
Section: Lucerne Transient Streak Virus (Ltsv) Occurs Inmentioning
confidence: 98%
See 2 more Smart Citations
“…The possibility that some viral satellites utilize host-encoded enzyme(s) for their replication was recently suggested by us (Linthorst & Kaper,t984a), and by Jones & Mayo (1984), along with the suggestion that if so, then the satellites' dependence upon their helper viruses would have to be attributed to some function relating to the intercellular movement and systemic spread of the helper throughout the plant. One approach towards resolving this question would be to see whether certain viral satellites are capable of independent multiplication in protoplasts, which does not necessitate spread from cell to cell.…”
mentioning
confidence: 99%